Inflation! The Battle Between Creditors and Workers - Blair Fix (Economics from the Top Down, 2023)
I've been writing about inflation for the better part of three months. It's been exhausting. Most of my time has been spent debunking misconceptions promoted by mainstream economists. Fortunately, I'm ready to move on. What's interesting about inflation is not the fact that prices rise. What matters is that prices rise at different rates. In other words, inflation creates winners and losers — it redistributes income. In this post, I'll dive into the redistribution dynamics between wage workers and creditors. When inflation rears its head, both groups try to bolster their income. But they rarely have equal success. Looking at over two centuries of US price history, I find (perhaps surprisingly) that inflation tended to benefit workers at the expense of creditors. Since the 1970s, however, the reverse has been true; inflation has systematically benefited creditors at the expense of workers. So what changed? Two things. First, the US labor movement was crushed. Second (and far less discussed), US policy makers adopted a new way to `fight' rising prices. When inflation reared its head, central banks attempted to quell it by aggressively hiking interest rates. Today, it's received wisdom that this policy `works'. Of course, the policy does work — but not for its stated goal. Never mind `fighting inflation'. When you raise interest rates, you give creditors a raise. Framed in this light, it's unsurprising that inflation has recently become a boon for US creditors. Backed by monetarist ideology, the government is now dedicated to preserving the return on credit. When it comes to class struggle, there's nothing like having the sledgehammer of the state to back you up. With credit returns in mind, here's the road ahead. Before diving into the dynamics of class struggle, I'll take a quick look at the language used to describe rising prices. Next, I'll quantify the price struggle between creditors and workers. Finally, I'll measure how this struggle has changed over time, and how it relates to the ideological currents of the period.
Keywords: P00; P1; E3; E31; D3; J3; D74; E5; 330; creditors; inflation; interest rates; inflation; wages